Rehabilitasi, Bukan Penjara: Solusi Restorative Justice untuk Penyalahguna Narkotika - Harry Fauzi; Bohari Muslim; Yanti Arnilis; Magfirah Magfirah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Drug abuse is a serious problem that not only affects individuals, but also threatens social stability and public health. In response to this problem, the concept of Restorative Justice emerged as a humane alternative that focuses more on restoring the physical, mental and social conditions of the offender. This theoretical study shows that rehabilitation through the Restorative Justice approach is a more humane, effective, and sustainable solution in dealing with drug abusers compared to the conventional prison approach. This research uses a normative juridical research method that is descriptive and analytical, with a library research approach. This method was chosen to examine in depth the concept, regulation, and application of rehabilitation as a restorative justice solution in handling drug abusers. The data used consists of primary data, namely laws and regulations related to narcotics, rehabilitation, and restorative justice, such as the Narcotics Law, Attorney General Regulation Number 18 of 2021, and Police Regulation Number 8 of 2021.Secondary data are academic literature, scientific journals, books, articles, and official documents that discuss rehabilitation and restorative justice in the context of narcotics abuse. Data collection techniques are collected through documentation studies and literature studies. Data analysis used qualitatively consists of normative juridical analysis to examine legal provisions and regulations governing rehabilitation and restorative justice. In Indonesia, the application of rehabilitation as a restorative justice solution has been regulated in various regulations, such as the Narcotics Law, Attorney General Regulation Number 18 of 2021, and Police Regulation Number 8 of 2021. These regulations provide a legal basis for rehabilitation as an alternative to punishment that prioritizes recovery and social reintegration.